Pre-disaster planning and preparedness for floods and droughts: A systematic review. (August 2019) - Raikes, Jonathan; Smith, Timothy F.; Jacobson, Christine; Baldwin, Claudia
Abstract: Increasing intensity and frequency of climate-related disasters such as floods and droughts challenge existing governance models of disaster risk reduction. This paper systematically reviews 147 articles on pre-disaster planning and preparedness for floods and droughts in developed countries. The results show: 1) the formal adoption of an integrated system of disaster risk reduction and human development remains fragmented due to a lack of legislative and policy frameworks; 2) there is a trend toward the privatization of risk management by devolving responsibility for disaster liability to landowners; 3) planning and preparedness is more common for floods than droughts in the disaster literature; and 4) flood management is increasingly risk-oriented, whereas drought management in the disaster literature remains dominated by a crisis management framework. Integration of pre-disaster planning and preparedness with human development initiatives requires further investigation to achieve Sustainable Development Goals (SDGs) at local, national and international scales.